Oral health status, self-perceived dental needs, and barriers to utilization of dental services among people with psychiatric disorders reporting to a tertiary care center in Haryana - Girish M Sogi; Sami Ahmed Khan; Manish Bathla; Jasneet Sudan (Wolters Kluwer Medknow Publications, 2020)
Background: Patients with psychiatric disorders can be vulnerable to oral diseases due to the adverse effects of medications and disease per se. The aim of this study is to assess oral health status, self-perceived dental needs, and barriers to utilization of dental services along with evaluation of intervention urgency among psychiatric patients. Materials and Methods: In this cross-sectional study, 165 individuals were examined at the psychiatric outpatient department of a tertiary care center. Clinical examination [dentition status and community periodontal index (CPI) modified] was done according to the World Health Organization Basic Oral Health Surveys, 2013. Other information was collected by direct interview and all the data were recorded on a prestructured, validated pro forma. Data were analyzed using SPSS Software. The statistical significance was determined by analysis of variance (ANOVA) and level of significance was set at P < 0.05. Results: Although decayed, missing, and filled teeth (DMFT) and CPI-modified scores increased with increase in duration of illness, the difference was not statistically significant. Evaluation of self-reported attributes revealed that the majority of the individuals had reported dental pain (34.6%) as their dental problem, 39.6% visit dentist only when there is a dental problem, and 41.7% did not felt any need to visit dentist. The ANOVA of DMFT in relation to duration of illness (P > 0.062) and CPI-modified scores (P > 0.078) were not statistically significant. Although when intervention urgency was evaluated, 70.3% needed prompt treatment depending on their oral health assessment. Conclusion: The findings of this study suggest that oral health concerns of this marginalized section of the population are unrecognized and should be given prominence by psychiatrists.